Analysis Of Basic Coffee Knowledge Levels Of Millenials In Bandung - Hilmina, Dissy; Sudono, Agus (Gastronomy Tourism Journal, 2020)
Coffee is a beverage that has survived for a very long time as a staple drink that is of interest to the world community. In Indonesia, culture of coffee drinking can be found in all regions. This coffee drinking habit can be a drink for all people. In Bandung, many coffee shops start Â to emerge as a sign that the coffee industry is now entering the third wave of coffee. In addition, coffee drinkers' interest in coffee is also increasing. They interest in both the origin of the seeds, the process, and the presentation before the coffee can be served. This study tries to examine the level of basic coffee knowledge of millennials in Bandung, a place to explore business potential. Businesses that can be explored including the field of coffee plantations, postharvest coffee, or retail in the form of making coffee shops.